Management of antenatally diagnosed hydronephrosis in a child presenting later with urinary tract infections: A case report (Indian Journal of Case Reports, 2018)
Preservation of renal function remains the main goal of follow-up of a child with antenatal hydronephrosis. The question remains as to how long we need to follow these children. Even after several decades, the indications and timing of surgery in a newborn with hydronephrosis are still debated. Herewith, we report the case of a 9-year-old male child who was diagnosed to have hydronephrosis on antenatal scans and was managed conservatively postnatally who presented after 9 years with recurrent urinary tract infections.